Hubungan kebiasaan makan dan stres terhadap dispepsia mahasiswa kedokteran Universitas Palangka Raya - Larasaty, Anggie; Frethernety, Agnes; Mutiasari, Dian (Fakultas Kedokteran Universitas Palangka Raya, 2023)
Dyspepsia is gastrointestinal tract syndrome, common symptom of dyspepsia is heartburn. Eating habits and stress are among risk factors for dyspepsia. This study aims to determine relationship of eating habits and stress to dyspepsia in medical students, Palangka Raya University. This study is observational analytic with cross-sectional design. Sampling using simple random sampling. The results of the study in 100 respondents found 27 people with dyspepsia and 73 people who do not; 56 people with good eating habits and 44 with bad eating habits; 9 people with mild stress, 83 people with moderate stress, and 8 people with severe stress. This study used chi-square and fisher-exact test, the results there is no relationship between eating habits and dyspepsia (p-value 0.778 >α 0.10); there is no relationship between stress and dyspepsia (p-value 1.00 >α 0.10). This shows that there is no relationship between eating habits and stress to dyspepsia.